The evolution of chronic pain: Adjustment status following treatment for acute low back pain. - De Gagné, Théo A. (University of Ottawa (Canada), 1997)
This study examined predictors of continued pain status in a sample of injured workers presenting with acute low back pain with no previous reported injury. Self-reported pain and disability, depressive symptoms, and coping strategies were assessed at admission to a treatment program in an initial sample of 41 injured workers. At discharge, 29 subjects were available for analyses, 27 at 3-months, and 20 at 6-months post injury. Coping and adjustment variables were examined as predictors of continued pain three months following the acute episode of low back pain. A logistic regression analysis using treatment change scores (self-reported disability and depressive symptoms) significantly predicted continued pain and correctly classified 91% of cases. Analyses describing the relationship among post-treatment change variables and continued pain revealed two factors, Diverting Attention, and Active Cognitive Coping, which correctly classified 90% of the cases. Hence, psychological variables measured close to injury onset were related to subsequent adjustment. Descriptive analyses indicated that somatic focus was synchronous with the temporal gradient of pain. Specifically, somatic focus was observed to increase as the pain experience persisted. The correlation among self-reported disability and present pain intensity was greater at discharge compared to admission. These findings indicated that variables impacted upon by treatment may serve as predictors of the development of chronic pain. The role of cognitive-behavioral interventions designed to impact on psychological adjustment variables is discussed.
Keywords: Health Sciences, Rehabilitation and Therapy.